The land agent, 1700-1920 - Tindley, Annie; Reilly, Ciarán; Rees, Lowri Ann (Scotland's land., 2018)
This book brings together leading researchers of British and Irish rural history to consider the role of the land agent, or estate manager, in the modern period.